Design of the Lapindo Sidoarjo Mud Museum with a Metaphorical Architectural Approach - Azhar Dhika Winarto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The Lapindo Mud Disaster that occurred in Sidoarjo in 2006 has become one of the most phenomenal events in Indonesia, causing the sinking of 16 villages and drastic changes to the landscape and lives of the surrounding community. The aim of designing the Lapindo Mud Museum is as a solution to fulfill its function not only as a place to store artifacts and information, but also as a space for interaction and reflection for the community. The research method used is descriptive qualitative. Design using a metaphor approach, namely the preparation of planning and design concepts with several analyses, namely, urban analysis, site analysis, land use analysis, circulation analysis, wind direction analysis, sun direction analysis, noise analysis, several concept preparations. The research results show that the building design is used as a symbol of the Lapindo Mudflow and commemorates the victims and communities affected by the Lapindo Mudflow. With a metaphorical architectural approach, the museum is expected to overcome the boredom that often occurs during conventional museum visits and facilitate deeper interactions with visitors.